Vein Graft Tympanoplasty: How a Transiently Used Graft Material Transformed Middle Ear Surgery. (11th May 2021) - Smith, Blaine D.; Martin, Hannah L.; Francis, Howard W.; Cunningham, Calhoun D.
Abstract : The inception of medial grafting as a technique for tympanic membrane repair was a critical milestone in the history of otology. John Shea introduced the medial graft technique and the use of vein grafts for tympanoplasty in 1960 after realizing that the vein grafts that he used to repair the oval window after stapedectomy could also be utilized to repair tympanic membrane perforations. At the time, tympanoplasty often utilized skin grafts, which required placement of the graft lateral to the tympanic membrane annulus. Placement of the graft medial to the tympanic membrane annulus allowed for more efficient surgery and avoided the complications associated with lateral grafting, such as blunting and lateralization. The introduction of vein grafts in tympanoplasty prompted a fundamental shift in technique from lateral to medial grafting, paving the way for decades of innovation in tympanoplasty.